The BRadykinesia Akinesia INcoordination (BRAIN) Tap Test: Capturing the Sequence Effect. Issue 6 (25th June 2019) - Hasan, Hasan; Burrows, Maggie; Athauda, Dilan S.; Hellman, Bruce; James, Ben; Warner, Thomas; Foltynie, Thomas; Giovannoni, Gavin; Lees, Andrew J.; Noyce, Alastair J.
ABSTRACT: Background: The BRadykinesia Akinesia INcoordination (BRAIN) tap test is an online keyboard tapping task that has been previously validated to assess upper limb motor function in Parkinson's disease (PD). Objectives: To develop a new parameter that detects a sequence effect and to reliably distinguish between PD patients on and off medication. In addition, we sought to validate a mobile version of the test for use on smartphones and tablet devices. Methods: The BRAIN test scores in 61 patients with PD and 93 healthy controls were compared. A range of established parameters captured number and accuracy of alternate taps. The new velocity score recorded the intertap speed. Decrement in the velocity score was used as a marker for the sequence effect. In the validation phase, 19 PD patients and 19 controls were tested using different hardware including mobile devices. Results: Quantified slopes from the velocity score demonstrated bradykinesia (sequence effect) in PD patients (slope cut‐off −0.002) with 58% sensitivity and 81% specificity (discovery phase of the study) and 65% sensitivity and 88% specificity (validation phase). All BRAIN test parameters differentiated between on and off medication states in PD. Differentiation between PD patients and controls was possible on all hardware versions of the test. Conclusion: The BRAIN tap test is a simple, user‐friendly, and free‐to‐use tool for the assessment of upper limb motor dysfunction in PD, which now includes a measure of bradykinesia.